CHALLENGES IN THE IMPLEMENTATION OF LAW NUMBER 21 OF 2019 ON THE QUARANTINE OF ANIMALS, FISH, AND PLANTS IN PREVENTING THE ENTRY OF QUARANTINE FISH PESTS AND DISEASES IN NORTH SUMATRA - Muhammad Arif Suparman; Tamaulina Br. Sembiring (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Quarantine practices in Indonesia have evolved since the Dutch East Indies era and have undergone significant changes, particularly with the enactment of Law No. 21 of 2019. This law integrates animal, fish, and plant quarantine and aligns regulations with current issues. However, its implementation faces challenges, especially in preventing the entry of Quarantine Fish Pests and Diseases (HPIK), such as the case of Koi Herpes Virus in Lake Toba. This study aims to identify obstacles in preventing the entry of HPIK in North Sumatra Province. The research employs a normative legal approach with prescriptive methods and a statutory approach. Data were collected through literature studies and analyzed using a qualitative-descriptive method. The findings indicate that several direct and indirect factors hinder the implementation of Law No. 21 of 2019 in preventing the entry of HPIK in North Sumatra. These include suboptimal field implementation due to numerous unofficial entry points, insufficient human resources, inadequate facilities and infrastructure, ineffective education and outreach channels, and limited community involvement in regulatory formulation.